Fabrication of microstructured polymers by a simple biotemplate embossing method and their characterization - Şam Parmak, Ebru Devrim (Carl Hanser Verlag, 2016)
In this work, microstructures were developed on a polymer surface using an embossing process by utilizing the transverse section of a wood as a biotemplate/mold. Microstructured polymers obtained by the proposed practical method were characterized by optical microscope for rough imaging, by scanning electron microscope for morphological properties and by Fourier transform infrared spectroscopy for surface chemistry. Utilization of a fluoropolymer eliminates the anti-stick surface pre-treatment and facilitates intact demolding of polymer structures from micro-voids of the wood. The height of the polymer microstructures was measured as 4 to 6 mu m. Dimensions of the wood microvoids can be tuned via acid/base treatment process. A drastic increase in heights of polymer microstructures (26 mu m) was observed for the sample stamped by the acid/base treated biotemplate. The proposed method, which delivers well-organized microstructure patterns on fluoropolymer surfaces, can be utilized in the production of specialty surfaces, such as antibacterial, stick/anti-stick and water repellent.
Keywords: Biomimetic; biotemplate; fluoropolymer; embossing; microstructure